The Position of E-Health in Reshaping Doctor/Patient Communications - Ahmad Salimzadeh; Alireza Jalali-Farahani; Mohammadjavad Alishiri; Gholam Hossein Alishiri; Ali Ayoubian (Baqiyatallah University of Medical Sciences, 2016)
Accessibility to all levels of information technology has experienced rapid progress in recent years, particularly in the health sector. Rapid penetration into this technology has led to changes in lifestyles and changes in the working procedures of institutions. In 2014, the number of Internet users reached 3 billion, and this number is predicted to exceed 8 billion in 2018. Statistics estimate the number of Iranian users of the Internet to be about 45 million. In 2014, more than 80% of Internet users searched for health information. Today, the Internet plays a vital role in providing such health services as education, disease management, support, basic medical treatment decisions, and doctor-patient communication.